2014
DOI: 10.1111/bcpt.12219
|View full text |Cite
|
Sign up to set email alerts
|

Application of High‐Content Analysis in Clinical Cytology for Translational Safety Biomarkers of Drug‐Induced Toxicity for Lymphoma Chemotherapy

Abstract: Drug cytotoxicity detected by high-content analysis (HCA) of live, cultured, human hepatocytes concurs with human toxic potential. We assessed HCA effectiveness in vivo using human, lymphoma line (HuT-78) and blood cells from healthy dogs and lymphomatous dogs treated with anticancer drugs: cytarabine, arsenic trioxide (AT), doxorubicin and mitoxantrone. DNA was stained with Hoechst-33342, calcium with fluo-4, mitochondria with TMRM and cell permeability with toto-3. HuT-78 and canine blood lymphocytes were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Also, a role is played by the hormesis phenomenon (biphasic response), which is commonly manifested in both biological and toxicological settings with a frequency of about 40% [ 33 36 ]. Being a protective mechanism derived from metabolic adaptation to environmental stresses, hormesis has been shown to influence cell number, mitochondrial activity, nuclear area, intracellular calcium level, membrane permeability and other activities [ 7 , 37 , 38 ]. For example, hormetic effects have been observed in response to endogenous agonists, drugs and natural compounds, like daidzein, genistein, curcumin, naringin or resveratrol [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, a role is played by the hormesis phenomenon (biphasic response), which is commonly manifested in both biological and toxicological settings with a frequency of about 40% [ 33 36 ]. Being a protective mechanism derived from metabolic adaptation to environmental stresses, hormesis has been shown to influence cell number, mitochondrial activity, nuclear area, intracellular calcium level, membrane permeability and other activities [ 7 , 37 , 38 ]. For example, hormetic effects have been observed in response to endogenous agonists, drugs and natural compounds, like daidzein, genistein, curcumin, naringin or resveratrol [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lieggi et al reported an apparent equivalence between human HepG2 and human T-lymphocytes for the identification of cytotoxic agents, when comparing those cell lines for the assessment of anti-cancer drug cytotoxicity [ 37 ]. In addition, quite recently canine peripheral blood lymphocytes have also been demonstrated to be suitable in the detection and monitoring of in vivo drug toxicity by high-content analysis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Per Artursson also presented weaknesses of the current in vitro methodologies. To overcome these challenges, he presented recent approaches towards more quantitative predictions of drug exposure: for example, models for estimation of free drug concentration, proteomics-informed quantification of drug transport and metabolism, and in vitro predictions of drug-induced liver injury.The scientific programme included presentations of new technologies in cell toxicity testing including efficient and sensitive techniques of high-content screening (HCS) based on in vitro monitoring of biochemical and morphological responses of individual live cells to chemical stress in microtitre plates [2][3][4]. This technique can be further refined and developed for use in preclinical testing, diagnostic and prognostic testing as well as monitoring.…”
mentioning
confidence: 99%